Analysis of Students' Learning Style on English Speaking Ability at SMP UNISMUH Makassar - Andi Nirwana Burhanuddin; Maharida; Hijrah (English Language Teaching Methodology, 2023)
This research was a qualitative research and the research instrument used interview. The population of this research is the VIII grade students of SMP UNISMUH Makassar  in class B. The research sample was 20 students. The research instruments was consisting of 15 items questions of interview, and each of the 5   question to find out the students learning style, visual, auditory or kinesthetic. The result of the data show that there was a difference students’ learning style  in speaking ability.  Based on the result of interview in SMP UNISMUH Makassar class B, two students have visual learning style, ten students have auditory learning style,and  eight students have  khinestetic learning style.